Penerapan Bot Whats App dalam Pendaftaran dan Monitoring Pelayanan Jasa pada Kantor Notaris Menggunakan Rad - Putri Ramadhani; Muhammad Dedi Irawan; Aninda Muliani Harahap (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
The development of information technology has encouraged increased efficiency and effectiveness in various fields, including service delivery in notary offices. This research aims to develop and implement WhatsApp bot in the process of registration and monitoring of services at the notary office using the Rapid Application Development (RAD) approach. The RAD method was chosen because of its ability to produce applications quickly through intensive iteration and prototyping. The developed WhatsApp bot allows users to register for services, organise appointments, and monitor service status in real-time via text messages. The results of this implementation show that the WhatsApp bot can increase convenience and speed in the registration and monitoring process, reduce staff workload, and improve customer experience. The evaluation showed a high level of user satisfaction with the system, with quick responses and more organised services. The implementation of this WhatsApp bot is expected to be a model for the development of similar applications in various other service areas. In this research, it adds a WA BOT feature for customers to conduct consultations without having to come to the office. With this designed application, it can facilitate employees of the Adi Pinem S.H Notary Office in the registration and monitoring process in service services.